Cost-utility analysis of four common surgical treatment pathways for breast cancer. Issue 6 (June 2021) - Kouwenberg, Casimir A.E.; Mureau, Marc A.M.; Kranenburg, Leonieke W.; Rakhorst, Hinne; de Leeuw, Daniëlle; Klem, Taco M.A.L.; Koppert, Linetta B.; Ramos, Isaac Corro; Busschbach, Jan J.
Abstract: Background: The aim was to evaluate the cost-utility of four common surgical treatment pathways for breast cancer: mastectomy, breast-conserving therapy (BCT), implant breast reconstruction (BR) and autologous-BR. Methods: Patient-level healthcare consumption data and results of a large quality of life (QoL) study from five Dutch hospitals were combined. The cost-effectiveness was assessed in terms of incremental costs and quality adjusted life years (QALYs) over a 10-year follow-up period. Costs were assessed from a healthcare provider perspective. Results: BCT resulted in comparable QoL with lower costs compared to implant-BR and autologous-BR and showed better QoL with higher costs than mastectomy (€17, 246/QALY). QoL outcomes and costs of especially autologous-BR were affected by the relatively high occurrence of complications. If reconstruction following mastectomy was performed, implant-BR was more cost-effective than autologous-BR. Conclusion: The occurrence of complications had a substantial effect on costs and QoL outcomes of different surgical pathways for breast cancer. When this was taken into account, BCT was most the cost-effective treatment. Even with higher costs and a higher risk of complications, implant-BR and autologous-BR remained cost-effective over mastectomy. This pleas for adapting surgical pathways to individual patient preferences in the trade-off between the risks of complications and expected outcomes.